The biomechanics of concussive helmet-to-ground impacts in the National Football league. (23rd January 2020) - Kent, Richard; Forman, Jason; Bailey, Ann M.; Funk, James; Sherwood, Chris; Crandall, Jeff; Arbogast, Kristy B.; Myers, Barry S.
Abstract: This paper presents a detailed characterization of helmet-to-ground impacts in the National Football League. Video analysis was performed for 16 head-to-ground impacts that caused concussions. Average resultant closing velocity was 8.3 m/s at an angle nearly 45° to the surface. Preimpact rotational velocity of the helmet ranged from negligible to as high as 54.1 rad/s. Helmet impacts were concentrated on the posterior and lateral aspects. To study the interaction in greater detail, a helmeted anthropomorphic test device (ATD) was launched over a football field and fell to the ground in various impact conditions. Substantial decoupling between the helmet and the head was observed, such that the head rebounded within the helmet and underwent changes in linear and rotational motion greater than those of the helmet. Vertical helmet rebound was also observed; the helmet underwent a change in vertical velocity on average 24% greater than the vertical component of its closing velocity. Frictional interaction between the helmet and the ground surface caused the helmet to undergo an average horizontal change in velocity of 57% of the horizontal component of its closing velocity. Finally, the duration of a helmet-to-ground impact was generally in the range of 15 – 30 ms, suggesting that the impact surface provides little ride-down. Lengthening this duration could be beneficial both by reducing the peak linear and rotational acceleration and by shifting the impact toward a time regime where brain strain is related to rotational acceleration rather than rotational velocity.